Pendampingan Pembuatan Legalitas Usaha Nomor Induk Berusaha (NIB) Kepada Pelaku Usaha Mikro Di Kelurahan Sentul, Kota Blitar - Vivia Nur Salsabila Trisnalia; Sonja Andarini (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The existence of Micro, Small and Medium Enterprises (MSME) to date cannot simply be ignored or abolished. As MSMEs are required to be able to compete in the free market era. As for being able to compete in this free market era, one of the conditions is the fulfillment of business legality. However, the management of business legality is still unknown to the public, especially MSMEs. As felt by Mr. Pur as the owner of Traditional Jamu MSMEs. Therefore, the purpose of this devotion activity is to assist MSMEs in understanding and accompanying the creation of the Business Identification Number (BIN) as the basis of business legality. The method used is observation, by visiting the MSMEs to find out directly what obstacles are faced by MSMEs. The result of this devotion activity is that Pak Pur's traditional herbal business already has legal legal legality, namely the Business Identification Number (BIN).